Phosphodiesterase Type 5 Inhibitors Synergize Vincristine in Killing Castration-Resistant Prostate Cancer Through Amplifying Mitotic Arrest Signaling - Hsu, Jui-Ling; Leu, Wohn-Jenn; Hsu, Lih-Ching; Ho, Chen-Hsun; Liu, Shih-Ping; Guh, Jih-Hwa (Frontiers in Oncology, 2020)
Combination therapies that display cancer killing activities through either coexistent targeting of several cellular factors or more efficient suppression of a specific pathway are generally used in cancer treatment. Sildenafil, a specific phosphodiesterase type 5 (PDE5) inhibitor, has been suggested to display both cardioprotective and neuroprotective activities that provide a rationale for the combination with vincristine on the treatment against castration-resistance prostate cancer (CRPC). In the present work, vincristine arrested cells in the metaphase stage of mitosis. Vincristine-induced mitotic arrest was identified by Cdk1 activation (i.e., increased Cdk1Thr161 phosphorylation and decreased Cdk1Tyr15 phosphorylation), cyclin B1 up-regulation and increased phosphorylation of multiple mitotic proteins and stathmin. Sildenafil synergistically potentiated vincristine-induced mitotic arrest and a dramatic increase of mitotic index. Furthermore, sildenafil potentiated vincristine-induced mitochondrial damage, including Mcl-1 downregulation, Bcl-2 phosphorylation and downregulation, Bak upregulation and loss of mitochondrial membrane potential, and sensitized caspase-dependent apoptotic cell death. Sildenafil-mediated synergistic effects were mimicked by other PDE5 inhibitors including vardenafil and tadalafil, and also by PDE5A knockdown in cells, suggesting PDE5-involved mechanism. Notably, sildenafil amplified vincristine-induced phosphorylation and cleavage of BUBR1, a protein kinase in spindle assembly checkpoint (SAC) function and chromosome segregation. Sildenafil also significantly decreased kinetochore tension during SAC activation. Moreover, sildenafil synergized with vincristine on suppressing tumor growth in an in vivo model. In conclusion, the data suggest that sildenafil, in a PDE5-dependent manner, potentiates vincristine-induced mitotic arrest signaling and sensitizes mitochondria damage-involved apoptosis in CRPC. Both in vitro and in vivo data suggest the combination potential of PDE5 inhibitors and vincristine on CRPC treatment.